The social impact bond as a financial instrument - Wiśniewski, Marcin (Obligacja społeczna jako instrument finansowy, 2018)
Social impact bonds are an innovative mechanism for financing social tasks with the financial resources of private investors. The repayment of the capital invested and capital gains depends on obtaining a predetermined social aim that is paid for by the public side under the “payment for results” formula. The previous work on this mechanism focused mainly on its task and organizational dimension. In this paper, the author attempts to define the social impact bond as a financial instrument. In particular, the financial side of the mechanism is considered. First, an attempt is made to determine the place of the social impact bond in the theoretical classifications of financial instruments. Second, the place of the instrument is indicated in the system of financial law. Finally, some remarks are made on the need to have the new instrument regulated in Polish legislation
Financial Sciences. Nauki o Finansach, 2018, vol. 23, no. 4, s. 102-117
Keywords: social impact bonds; financial instruments; bonds; public management